Whistleblowing: a western and Shari’ah perspective = Pemberi maklumat: perspektif barat dan Shari‘ah - Zainudin, Nur Hazirah; Wan Zahari, Wan Mohd Zulhafiz (IIUM Press, International Islamic University Malaysia, 2018)
The concept of whistleblowing law in Islam is unique and differs from the West as it derives from the elements of Tawhid and Shari’ah. The concept is essentially dynamic and relevant since it was initially introduced during the Islamic ruling era until the present time. The practice of whistleblowing in Islam maintains the public interest (maslahah ‘ammah) which aims in fulfilling the five objectives of Maqasid Shari’ah. On the other hand, the western whistleblowing law was developed in response to tragedies in assuring good governance and protecting the public interest, in which the ideas of good and bad are determined by social norms and not based on the scriptures. In the present time, notably, the role of whistleblower is significant to response to corruption as a global issue plaguing many nations, which causes substantial destruction to social, economic and political aspect. In this regard, the purpose of this paper is to explore and compare the concept and scope of disclosure of whistleblowing law from Shari’ah perspective and its western counterpart and how its principled conviction, upholding public interest disclosure could deal with the current phenomenon plaguing many nations, corruption. With that, the methodology employed in this paper reflected the descriptive, analytic, and prescriptive approaches by analyzing the existing laws, decided cases and literature pertaining to the conceptual and the legal frameworks of whistleblowing under the Western and Islamic jurisprudences.